‘You have to call the right name' – Operation Joshua meets Cosmology and Catholicism at Lake Chambri in Papua New Guinea - Falck, Christiane (The Australian journal of anthropology, 2020)
In the Sepik, names feature centrally in political and religious contexts. Esoteric knowledge about totemic names enables Nyaura men to achieve status and power and can set them in contact with spirits. A recently arrived Pentecostal/evangelical movement—Operation Joshua—claims to have found the true name of God, whom it presents as being radically different to the beings people's ancestors have known. At Lake Chambri, however, the Nyaura (West Iatmul) community Timbunmeli had accommodated Catholicism to their culture long before Operation Joshua came to their village. While Operation Joshua demonizes Nyaura spirits, the Catholic community understands God to be an ancestral being for whom different clans know different names. Taking a political ontology perspective, I analyze the encounter of Operation Joshua and Nyaura Catholicism in Timbunmeli in relation to cosmo-ontological politics pursued by ambitious Nyaura men and different denominations. I suggest that denominational pluralism creates ontological pluralism in Timbunmeli, where different actors engage different truth claims concerning the being and reality of central Christian figures in their world-making practices.